Visual evoked potentials to an illusory change in brightness: the Craik–Cornsweet–O'Brien effect. Issue 10 (6th July 2016) - Suter, Steve; Crown, Nik
Abstract : Can brain electrical activity associated with the Craik–Cornsweet–O'Brien effect (CCOB) be identified in humans? Opposing luminance gradients met in the middle of a square image to create a luminance contrast-defined vertical border. The resulting rectangles on each side of the border were otherwise equiluminant, but appeared to differ in brightness, the CCOB effect. When the contrast gradients were swapped, the participants perceived darker and lighter rectangles trading places. This dynamic CCOB stimulus was reversed 1/s to elicit visual evoked potentials. The CCOB effect was absent in two control conditions. In one, the immediate contrast border, where the gradients met, was replaced by a dark vertical stripe; in the other, the outer segments of both rectangles, where the illusion would otherwise occur, were replaced by dark rectangles, leaving only the contrast-reversing gradients. Visual evoked potential components P1 and N2 were present for the CCOB stimuli, but not the control stimuli. Results are consistent with functional MRI and single unit evidence, suggesting that the brightness of the CCOB effect becomes dissociated from the luminance falling on the eye early in visual processing. These results favor explanations of brightness induction invoking rapid, early amplification of very low spatial-frequency information in the image to approximate natural scenes as opposed to a sluggish brightness adjustment spreading from the contrast border.